Developing of an applied reading application with family interaction approach and its effectiveness on Expressive language;Receptive Language;Spoken language( spoken language skills) of children with down syndrome - kosar bereyhi (Ravānshināsī-i Afrād-i Istis̠nāyī, 2017)
Abstract Objective: this study aimed to design an creative educational application for family-centered reading and evaluation of its effectiveness in reading skills among the slow-paced students with Down syndrome. Methods: this applied semi-experimental study is a per-test-post-test project, follow-up with the test and control groups. Twenty slow-paced students with Down syndrome were randomly selected and assigned in two test and control groups. Wechsler IQ test, TOLD test and Peabody Picture Vocabulary Test (PPVT) were run for students in the per-test, and TOLD test was run in the post-test and a half month after follow-up stage. Results were analyzed with Analyze of Co-variance (ANCOVA) and repeated measures analysis. Results: in general, results showed a significant difference in reading between test and control groups and the difference remained sustainable in the follow-up stage. Conclusion: innovation in family- centered reading application was effective in increase in reading skills among the slow-paced students with Down syndrome and this effect remained sustainable. Education by new technologies in the form of software for children with Down syndrome should be seriously considered. Family- centered reading application Can be used for teaching children, families and educators.